PENINGKATAN INTEGRASI RISET DAN INOVASI DENGAN KEBIJAKAN PEMBANGUNAN DAERAH PADA BADAN PERENCANAAN PEMBANGUNAN, RISET DAN NOVASI DAERAH KABUPATEN SIKKA - Selviana Evarista Misa; Imanuel Wellem; Viktor Eko Transilvanus (Jurnal Projemen UNIPA, 2026)
The integration of research and innovation in regional development policy is an important aspect of realizing effective, adaptive, and evidence-based planning. However, in practice, the utilization of research results in the policy formulation process at the regional level has not been optimal, causing policies to be frequently formulated based on intuition, experience, or administrative considerations alone. This condition is also found at the Regional Development Planning, Research, and Innovation Agency (BAPPERIDA) of Sikka Regency, which has a strategic role in coordinating regional planning, research, and innovation. This study aimed to analyze the level of integration of research and innovation with regional development policies, identify inhibiting factors, and formulate strategies to enhance integration in a more effective and sustainable manner. The theoretical review of this study refers to the concepts of organizational integration, research as a basis for decision-making, public innovation, and the regional innovation system approach. The method used was a descriptive qualitative approach conducted through internship activities, with data collection techniques including observation, interviews, documentation, and literature review. Data were analyzed descriptively by comparing empirical conditions with the established conceptual framework. The results of the study show that integration has been implemented through the alignment of research with regional planning documents, facilitation of cross-sector collaboration among regional agencies and universities, and the utilization of several research outputs for policy formulation. Nevertheless, obstacles remain, including limitations in human resources, budget, research infrastructure, cross-sector coordination, and the suboptimal innovation culture. Therefore, strengthening regulations, improving institutional capacity, developing an innovation ecosystem, and integrating research data systems are required to ensure that development policies are more targeted and sustainable. Overall, the integration of research and innovation plays an important role in improving the quality of regional development governance in Sikka Regency.